Calcium digestibility of inorganic sources for laying hens - Diana, Thiago Ferreira (2022)
Two independent experiments were conducted in order to determine the digestibility of calcium from different inorganic sources. Experiment one: The apparent calcium (Ca) digestibility coefficient (ADC) and true digestibility coefficient (TDC) of different inorganic calcium sources were determined in laying hens of different ages. Three Ca digestibility tests were carried out, each assessing 240 Lohmann Brown lineage laying hens distributed in a com-pletely randomized design. Nine dietary treatments were arranged in a 3 × 3 factorial design consisting of three ages (40, 50 and 70 weeks) × three Ca (dicalcium phosphate (DCP) sources, fine (FL) and coarse (CL)) limestone, comprising eight replicates per treatment of six birds per experimental unit. Regarding the DCP, the ADC was higher (P < 0.05) in 40-week- old birds. The DCP ADC for 40-, 50- and 70-week-old birds was 0.889, 0.613 and 0.712, respectively. No effect (P > 0.05) of age on the ADC was noted for either FL or CL. Comparing Ca sources, DCP exhibited a higher (P < 0.05) ADC (0.889), followed by FL (0.699) and CL (0.515), in 40-week-old birds. DCP (0.712) and FL (0.652) presented (P < 0.05) higher ADC compared to CL (0.482), in 70-week-old birds. No effect of Ca sources at 50 weeks on the ADC was observed (P > 0.05). Endogenous loss values of 790, 860 and 930 mg.kg −1 of consumed dry matter were observed at 40, 50 and 70 weeks, respectively. For the TDC, no interaction (P > 0.05) was observed between Ca sources and bird age. The highest TDC value (P > 0.05) was found in birds fed DCP (0.786) followed by FL (0.637) and CL (0.534). In addition, birds at 40 weeks of age (0.714) exhibited higher TDC values (P < 0.05) compared to animals at 50 weeks of age (0.608). The findings reported herein demonstrate that the true digestibility is greater in the youngest birds and that consumed the DCP and the FL in relation to the birds that consumed the CL. Experiment two: The objective of this study was to determine the apparent retention and digestibility coefficients of Ca in limestone of different granulometries, in laying hens. A total of 288 Lohmann Brown laying hens (50 weeks of age; 1,964 ± 98 g) were distributed in a completely randomized experimental design with a 3 × 2 factorial arrangement [three Ca concentrations (10, 20, and 30 g kg-1) × two limestone granulometries (480 and 1978 μm) ]. Eight repetitions per treatment, with six birds per experimental unit. The duration of the experiment included five days each of adaptationand total excreta collection. At the end of the 10-day period, all birds were slaughtered and the ileal contents were collected. The total or ileal Ca content was plotted against the Ca of diets concentration using linear regression analysis. The slope of the regression line represented the apparent retention (CaR) and digestibility coefficients of Ca (CaD) in limestone. An interaction was found between Ca concentration in the diet and limestone granulometry on CaD (p = 0.001) and CaR (p < 0.001). The CaD of fine- and coarse-grained limestone increased linearly with increasing Ca concentrations in the diet. The CaR of fine- and coarse-grained limestone increased linearly with increasing Ca concentrations in the diet. The apparent digestibility coefficients estimated for laying hens fed fine-grained and coarse- grained limestone were 0.72 and 0.35, respectively. The apparent retention coefficients estimated for laying hens fed fine-grained and coarse-grained limestone were 0.96 and 0.47, respectively. Keywords: Calcitic Limestone. Dicalcium phosphate. Granulometry. Regression.